2018
DOI: 10.1080/14670100.2018.1505324
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Cochlear Mini Microphone (MM) as a personal radio system (FM) with young children who are deaf

Abstract: The insights gained into the challenges and benefits of the MM for this population offered explanations for the limited take-up of the equipment and informed ways to encourage appropriate use Discussion: Equipment issued to very young children works best alongside specific advice and training, targeted at both families and local professionals. Despite some technical limitations, the availability of a personal radio system was found to be of benefit by some families. It encouraged consideration by both families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Research by Jantien et al (2017) showed that using a wireless remote microphone in a noisy environment improved Speech Reception Thresholds (SRTs)in adults with bilateral cochlear implants by 5.4 dB. In a study with preschool children using remote microphones as personal wireless systems with cochlear implants, Clare and Gill (2018) showed that with professional guidance and training at home, this technology has the potential to improve education and communication environments for preschool children. In the present study, the benefit of using the remote microphone was consistent in all three test distances for both adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Jantien et al (2017) showed that using a wireless remote microphone in a noisy environment improved Speech Reception Thresholds (SRTs)in adults with bilateral cochlear implants by 5.4 dB. In a study with preschool children using remote microphones as personal wireless systems with cochlear implants, Clare and Gill (2018) showed that with professional guidance and training at home, this technology has the potential to improve education and communication environments for preschool children. In the present study, the benefit of using the remote microphone was consistent in all three test distances for both adults and children.…”
Section: Discussionmentioning
confidence: 99%